Effects of Metamaterial Slabs Applied to Wireless Power Transfer at 13.56 MHz - Gunyoung Kim; Taek-Kyu Oh; Bomson Lee (International Journal of Antennas and Propagation)
This paper analyzes the effects of a metamaterial slab (or a practical “perfect lens”) with negative permeability applied to a two loop magnetically coupled wireless power transfer (WPT) system at 13.56 MHz, based on theory, full-wave electromagnetic- (EM-) simulations, and measurements. When using lossless slabs with ideal negative permeability in EM-simulations, the WPT efficiencies have been found to be enhanced close to 100% due to the magnetic field focusing. For the case of using a realistic slab made of ring resonators (RR) μr=-1-j0.23 with s/d=0.5 (s: slab width, d: distance between the transmitting and receiving loops), the WPT efficiency has been found to significantly decrease to about 20%, even lower than that of a free space case (32%) due to the heavy power absorption in the slab. However, some efficiency enhancement can be achieved when s/d is optimized between 0.1 and 0.3. Overall, the significant enhancement of efficiencies when using a lossless slab becomes moderate or only marginal when employing a realistic slab.